PELATIHAN PEMANFAATAN BATANG PISANG (KRIBANG) KERIPIK BATANG PISANG MENJADI PRODUK LOKAL BERNILAI EKONOMI DITENGAH PANDEMI COVID 19 DI KELURAHAN LOPIAN KABUPATEN TAPANULI TENGAH - Nur Simamora, Fauziah; Ainun Hasibuan, Nur; Hutagalung, Heriyawan (COVIT (Community Service of Tambusai), 2022)
The impacts arising from the COVID-19 Pandemic on economic activity after the enactment of government regulations in preventing the spread of COVID-19, namely: community income (traders, fishing facilities and farmers) is decreasing, many economic activities are closed, community and regional economies are declining , the market price of agricultural products is falling, and basic needs are increasing. Likewise in the Lopian village, Badiri sub-district, Central Tapanuli regency, the community is increasingly difficult in terms of the economy due to the impact of this pandemic. Many housewives who only have time to take care of the house, many fishermen those who do not get proper fish catches and school children who have to study at home due to this pandemic. With the current conditions, a form of service has been created that can provide a positive movement for the Lopian village community, especially housewives who live in the village. . Utilization of banana plant parts from roots to leaves, especially the fruit consumed by the community. Meanwhile, other parts of the banana plant, namely the heart, stem, fruit skin, and weevil are rarely used and are simply thrown away as banana waste. The implementation of community service activities in the form of counseling and demonstrations of making banana stems in the Lopian sub-district was carried out with the Steps of Preparation. Tools: knife, chips, basin, cutting board, blender, stove and frying pan. Procurement of materials: banana stems, flour, cornnae flour, water , spices, salt.Packaging and labeling (kribang)banana stem chips, Implementation Phase Determine the training participants (kribang) banana stem chips (kribang)banana stem chips and discussion with the community about planning (kribang)banana stem chips to be used which prioritizes the favorite type of banana and the most common in the local location.Monev and Reporting, Reporting, Work stages are carried out after completion of training (kribang) for banana stem chips from community groups in Lopian sub-district. Preparation of activity reports and follow-up monitoring. Keywords: Banana stems, Community Service